PRIMING OF GENETIC VARIATIONS BY COLOCYNTH FRUIT EXTRACT AND CALLUS INITIATION IN EMBRYOS OF TWO CULTIVARS OF ALFALFA SEEDS - & Ali, Hamza (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
An experiment was conducted at Central lab of Graduate studies, College of Agriculture, University of Baghdad during 2015-2016. The aim was to study the effect of colocynth fruit extract on inducing callus from embryos of two alfalfa cultivars were PAC-78001 and local variety by tissue culture technique using factorial experiment within CRD. Seeds was soaked with colocynth fruit extract at 0, 75, 150, 225, and 300 ml Li-1 for 24 hours, then, sterilized by NaOCl at 4.5% for 15 minutes. The results showed significant differences between two cultivars responding to colocynth fruit extract levels. Concentration at 150 ml Li-1 gave the highest both fresh and dry weight of callus (205.90 and 20.60) respectively. Also, PCR results depending on RAPD and electrophoresis for DNA samples which isolated from callus of two cultivars and subjected to various concentrations of colocynth fruit extract 0, 75, 150, 225 and 300 ml Li-1 showed differences in amplified observed bands, molecular weights and brightness intensity by using primers primer -Y07, -Y06, OE-12, C-08, D-10, -Y10 and A-16, and There was no difference in bands number at all concentrations of colocynth fruit extract for local variety by primer A-16.